Computer-Assisted Transcatheter Heart Valve Implantation in Valve-in-Valve Procedures. Issue 3 (May 2016) - Soulami, Réda Belhaj; Verhoye, Jean-Philippe; Duc, Hung Nguyen; Castro, Miguel; Auffret, Vincent; Anselmi, Amedeo; Haigron, Pascal; Ruggieri, Vito Giovanni
Objective: Valve-in-valve (ViV) procedures are increasingly being considered as an alternative to redo surgery for the treatment of degenerated bioprosthetic heart valves in patients with excessive reoperative risk. The objective of our study was to evaluate the feasibility of computer guidance in transcatheter heart valve (THV) implantation during ViV procedures. Methods: Preprocedural electrocardiogram-gated computed tomography–scan images were processed using semiautomatic segmentation of the degenerated bioprosthesis' radiopaque landmarks and of the ascending aorta. Virtual three-dimensional (3D) reconstructions were created. A virtual plane was subsequently added to the 3D reconstructions, indicating the optimal landing plane of the THV inside the tissue valve. Within a hybrid operating theater, a 3D/2D registration was used to superimpose the 3D reconstructions, while dynamic tracking was allowed to maintain the superimposition onto the fluoroscopic images. The THV was afterward implanted according to the optimal landing plane. Projection of the ascending aorta and the coronary arteries was used to assess the risk of coronary ostia obstruction. Results: Between January 2014 and October 2014, nine patients underwent aortic ViV procedures in our institution. Among those nine patients, five procedures were retrospectively evaluated as a validation step using the proposed method. The mean (SD) superimposition error was 1.1 (0.75) mm. Subsequently, two live cases were prospectively carried out using our approach, successfully implanting the THV inside the degenerated tissue valve. Conclusions: Our study demonstrates the feasibility of a computer-guided implantation of THV in ViV procedures. Moreover, it suggests that augmented reality may increase the reliability of THV implantation inside degenerated bioprostheses through better reproducibility.